The militant cinema - Oroz, Silvia (Nawi, 2022)
In this paper, some fragments of memory will be outlined around political militancy in the form of cinema in the 1960s and 1970s in Argentina, through personal testimonies on the collective production of Informes y testimonios: la tortura política en Argentina (1966-1972).